EFEKTIVITAS MEDIA VIDEO DAN LEAFLET TERHADAP PENINGKATAN PENGETAHUAN SISWA DI SMAN 05 KOTA JAMBI TENTANG BAHAYA ROKOK ELEKTRIK - M. Zhillan Umaradhiefa Ardhiansyah; Puspita Sari; Muhammad Rifqi Azhary; Oka Lesmana S; Vinna Rahayu Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of electronic cigarettes among adolescents continues to increase and poses a risk of health problems, making effective educational media necessary to improve students’ knowledge. This study aimed to assess the effectiveness of video and leaflet media in improving students’ knowledge regarding the dangers of electronic cigarettes at SMAN 05 Kota Jambi. This study used a quasi-experimental design with a two-group pretest-posttest approach. The sample consisted of 97 students selected using accidental sampling. Data were collected through a knowledge questionnaire administered before and after the intervention, then analyzed using univariate and bivariate analysis with the Wilcoxon and Mann-Whitney tests. The results showed a significant increase in knowledge in both groups after the intervention. The leaflet group’s average score increased from 87.75 to 97, while the video group increased from 81.94 to 94.86, with a p value <0.001 in each group. Although the average increase in the video group was higher, the difference in effectiveness between the video and leaflet media was not statistically significant (p = 0.229). In conclusion, both video and leaflet media were equally effective in increasing students’ knowledge about the dangers of electronic cigarettes, with no significant difference in effectiveness between the two media.